In situ formed N-containing copper nanoparticles: a high-performance catalyst toward carbon monoxide electroreduction to multicarbon products with high faradaic efficiency and current density. Issue 19 (6th May 2022) - Du, Huitong; Liu, Li-Xia; Cai, Yanming; Wang, Ying; Zhang, Jian-Rong; Min, Qianhao; Zhu, Wenlei
Abstract : The in situ -derived N-containing catalyst from cuprous 7, 7, 8, 8-tetracyanoquinodimethane presents remarkable ECOR performance with a high FE of 81.31% towards multi-carbon products at −0.69 V vs. RHE in 1.0 M KOH. Abstract : Developing efficient catalysts for electrochemical carbon monoxide reduction (ECOR) with high faradaic efficiency (FE) and current density is highly desirable. In this work, we demonstrate that the N-containing Cu nanoparticles formed in situ by the reconstruction of cuprous 7, 7, 8, 8-tetracyanoquinodimethane possess high-performance ECOR ability. Impressively, the N-containing Cu nanoparticle catalyst presented the highest FE of 81.31% towards multicarbon products with a high commercial-grade partial current density of 162.62 mA cm −2, which is among the best of the reported Cu-based ECOR catalysts at −0.69 V versus the reversible hydrogen electrode. The retained ligand on the formed catalyst via the convenient in situ formation is crucial for the selectivity of multicarbon products. This work will arouse enthusiasm for the utilization of reconstruction features for designing ligand-containing catalysts with enhanced artificial carbon fixation ability.